Karydakis Flap Procedure in Patients with Sacrococcygeal Pilonidal Sinus Disease: Experience of a Single Centre in Istanbul - M. Kamil Yildiz; Erkan Ozkan; Hacı Mehmet Odabaşı; Bülent Kaya; Cengiz Eriş; Hacı Hasan Abuoğlu; Emre Günay; Mehmet M. Fersahoglu; Süleyman Atalay (The Scientific World Journal)
Background. The aim of this retrospective study was to evaluate the results of patients with sacrococcygeal pilonidal sinus who underwent surgery using the Karydakis technique. Methods. Two hundred fifty-seven patients with sacrococcygeal pilonidal sinus disease were treated by the Karydakis flap procedure between December 2003 and June 2011. Patients were evaluated with respect to age, gender, preoperative symptoms, duration of preoperative symptoms, history of pilonidal sinus surgery, early postoperative complications, recurrence rates, and cosmetic satisfaction. Results. There were 223 (86.8%) male and 34 (13.2%) female patients. The mean age of the patients was years. The most frequent symptom was seropurulent discharge (57.58%). Postoperative morbidity was noted in 24 patients (9.3%). The mean hospital length of stay was days. The cosmetic satisfaction rate was 91.06%. Recurrences were noted in 6 patients (2.3%). Conclusion. The Karydakis flap procedure is a safe treatment alternative for the surgical treatment of sacrococcygeal pilonidal sinus disease owing to the associated low complication rate, short hospital length of stay, rapid healing, and a high patient satisfaction rate.